Exploring Quality of Life Among Thyroid Patients in South Indian Communities: A Comprehensive Study (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The thyroid gland plays a crucial role in regulating metabolism and influencing a wide range of physiological functions through its hormone production, and thyroid disorders affect millions globally, significantly impacting individuals’ quality of life and overall health. Complications arising from thyroid diseases can vary widely, affecting both physical and emotional well-being, making a comprehensive evaluation of associated complications and quality of life essential. The primary objectives of this study were to evaluate complications related to thyroid disease and assess health-related quality of life in patients with thyroid disorders, while secondary objectives included addressing safety outcomes and providing structured guidance for newly diagnosed patients to counter misinformation and improve understanding of symptoms, causes, and treatments. Conducted at the Centre of Diabetes and Endocrine Care with ethical approval from the Pranav Diabetes Centre Ethics Committee and informed consent from all participants, the study employed a systematic search strategy to identify relevant data and evaluated patients through regular clinical and biochemical assessments. Data were analysed using Chi-square statistical tests to determine significance, and demographic factors such as marital status, residency, age, gender, weight gain, hair loss, and swallowing difficulties were examined. Quality of life evaluations revealed notable variations among thyroid patients, significantly affecting their physical and emotional well-being. The study highlighted higher occurrences of thyroid disorders among married individuals, urban residents, and non-working participants within the South Indian community, with common symptoms including weight changes, temperature sensitivity, fatigue, and variable swallowing difficulties. Factors such as healthcare access, socio-cultural influences, and treatment effectiveness were found to play crucial roles in patient well-being, underscoring the importance of tailored interventions and support systems to enhance quality of life. This research emphasizes the need for clear, structured information in research articles to guide newly diagnosed patients, helping them understand thyroid symptoms, causes, and treatments and ultimately improving their overall quality of life.